Seleção cultural e transmissão cultural no jogo Dilema do prisioneiro iterado - Pin, Stephanny Sato Del (2017)
The cooperation experiments discuss important parameters about the social behavior and the social environment, using the triple contingencies unit of analysis. The iterated prisoners dilemma game was repeatedly used as a procedure for experimental investigation into cooperation by behavioral analysts. The prisoners dilemma consists of the conflicting relation between individual gains and group gains. The combination of the choices among all those involved in the dilemma may lead to: losses for all, gains for all or loss for one while another gains. Such analyses of cooperation may be expanded when another unit of analysis – metacontingency – is used. This study sought replicate the work of Ortu et al. (2012), investigating the effect of cultural consequences on the selection of interlocking behavioral contingencies. Three modifications were made: 1) open groups were programmed – replacement of participants 2) the presentation of cultural consequences (market feedback) was made on a CRF schedule; and to contribute to the comprehension of verbal behavior in the selection by metacontingencies 3) the rules issued by the participants throughout the generations were analysed. Each of the three experimental groups, while in the experimental context, built a “cultural practice” as a form of coordination to obtain individual points and/or points of cultural consequences forecast in the various experimental conditions. Exposure to all experimentally programmed cultural consequences was possible for all groups. Groups 1 and 3 varied in the production of interlacements in initial generations, but on the whole met the required performance criteria, therefore they were consistent in the production of cooperational interlacements. Group 2 produced variable interlacements, the most consistent being XYYY and YYYX, i.e. “competitive” interlacements. The analysis of verbal interactions clarifies the reason behind such production: to obtain more points individually, group 2 coordinated themselves on a rotating schedule, whereby whoever chooses differently to the others would have a greater gain, while the others would have a medium gain, and would not receive any additional gain in the cultural consequence. The participants in group 2 obtained the total egalitarian gains and coordinated themselves with greater frequency from informative rules. Group 3 coordinated themselves with greater frequency from coersive rules and had unequal individual totals. The results of this study suggest that the selection of cooperation standards depends on the individuals consequences forecast in the more “traditional” procedures, but also depends significantly on external variables studied here: the production of cultural consequences contingent on aggregated products and the analysis of verbal interaction for the selection by metacontingencies